2010
DOI: 10.1303/aez.2010.609
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antimicrobial peptide genes from Japanese honeybee Apis cerana japonica (Hymenoptera: Apidae)

Abstract: Two antimicrobial peptide cDNA clones, abaecin (named AcjAba) and defensin (named AcjDef2) were isolated from the Japanese honeybee, Apis cerana japonica, using rapid amplification of cDNA end (RACE) methods. Deduced amino acid sequences of AcjAba and AcjDef2 in A. c. japonica showed high identity with those in the European honeybee, Apis mellifera (97.1%, and 93.0%, respectively). In the mature peptide region, only one amino acid residue (Val) of A. mellifera abaecin was replaced with (Ile) of A. c. japonica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Pathogen levels and genetic variability across intraspecies/interspecies of host species might affect immune responses to bacterial infection. Yoshiyama and Kimura (2010) could not observe transcript levels of abaecin and defensin2 in A. cerana japonica even though the larvae were challenged with numerous of P. larvae (100 spores/μL). Evans and Pettis (2005) suggested that higher immune response may not be worthwhile for the larvae because there was a developmental cost to defend themselves against pathogens and parasites that would decrease the production at the colony level.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Pathogen levels and genetic variability across intraspecies/interspecies of host species might affect immune responses to bacterial infection. Yoshiyama and Kimura (2010) could not observe transcript levels of abaecin and defensin2 in A. cerana japonica even though the larvae were challenged with numerous of P. larvae (100 spores/μL). Evans and Pettis (2005) suggested that higher immune response may not be worthwhile for the larvae because there was a developmental cost to defend themselves against pathogens and parasites that would decrease the production at the colony level.…”
Section: Discussionmentioning
confidence: 77%
“…Pathogen levels and genetic variability across intraspecies/interspecies of host species might affect immune responses to bacterial infection. Yoshiyama and Kimura () could not observe transcript levels of abaecin and defensin2 in A. cerana japonica even though the larvae were challenged with numerous of P. larvae (100 spores/μL).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is some conundrum whether this may impact the healing process when applying honey to the wound. These microorganisms cannot hinder the healing process since most of them have been identified as non-pathogenic which are from the Bacillus genus [58,59] and actinomycete Streptomyces [60]. In contrast, several notorious bacteria like Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Clostridium , and Coliform species tend to disturb the healing process [61,62].…”
Section: Antimicrobial Role Of Stingless Bee Honeymentioning
confidence: 99%